Water-based environment-friendly emulsion and application thereof in real stone paint coating
Through the modified sodium alginate microcapsules with benzotriazole chloride, the problem of oxidation and degradation of sodium alginate under ultraviolet light is solved, and the self-healing performance and durability of aqueous real stone paint coatings are improved.
Patent Information
- Application Number
- CN202510670881.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-08-05
AI Technical Summary
The existing water-based real stone paint coatings are easily oxidized and degraded by ultraviolet rays under outdoor conditions, resulting in a decrease in self-repair performance, affecting the decoration effect and service life.
The sodium alginate microcapsules are modified by acyl chloride benzotriazole, and the hydroxyl group of the surface of the sodium alginate microcapsules is retained by reacting benzotriazole with the hydroxyl group on the surface of the sodium alginate microcapsules, and the carboxy group is retained, and the benzotriazole is used to absorb ultraviolet energy to prevent the shell oxidation and rupture. At the same time, the sodium alginate microcapsules are modified by acyl chloride benzotriazole to release the repair material when the coating is ruptured.
Effectively maintain self-repair performance, improve the decorative effect and service life of real stone paint, strong aging resistance, good anti-pollution performance, dense and smooth surface, difficult to adhere to pollutants, strong adhesion, and difficult to peel off.
Smart Images

Figure BDA0005416363970000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of real stone paint, and specifically relates to a water-based environmentally friendly emulsion and application thereof in real stone paint. Background Art
[0002] Real stone paint is a coating that mimics marble and granite. Made primarily from natural stone powders of various colors, it's applied to building exteriors to create a simulated stone effect, hence the name "liquid stone." Buildings finished with real stone paint retain a natural, authentic color, making it suitable for both indoor and outdoor decoration. It's also fireproof, waterproof, acid- and alkali-resistant, and pollution-resistant, effectively protecting buildings from harsh environmental conditions and extending their lifespan.
[0003] Compared with solvent-based paints, water-based emulsion paints have the advantages of low VOC content, convenient construction, easy cleaning, and green environmental protection. However, existing water-based paints contain polar channels formed by hydrophilic groups, which will accelerate the penetration of corrosive substances such as water. Therefore, real stone paint based on water-based emulsion will reduce the corrosion resistance and durability of the anti-corrosion coating it forms.
[0004] The Chinese patent with announcement number CN116426193B announces a water-based environmentally friendly anti-corrosion coating. This solution uses sodium alginate / acrylic acid / acrylamide styrene acrylic emulsion copolymer and water-based epoxy resin as the coating matrix, in which the sodium alginate is not polymerized. It runs through the acrylic acid / acrylamide polymer in a chain structure, which improves the elasticity of the polymer material. At the same time, it has swelling properties. When the coating is defective after long-term physical action, it can swell, thereby improving the density and self-healing properties of the coating.
[0005] However, sodium alginate is easily oxidized and degraded by ultraviolet rays under outdoor conditions, which leads to a decrease in the self-repairing performance of the above-mentioned anti-corrosion coating and makes it difficult to effectively repair the cracks in the coating, thereby affecting the decorative effect and service life of the real stone paint. Summary of the Invention
[0006] The object of the present invention is to provide an aqueous environmentally friendly emulsion and its application in real stone paint. The aqueous environmentally friendly emulsion is added with benzotriazole-modified sodium alginate microcapsules with sodium alginate as the shell layer and benzotriazole chloride grafted on the surface. Benzotriazole chloride can reduce the probability of oxidation and rupture of the sodium alginate shell layer, protect the repair material in the sodium alginate microcapsules, thereby effectively maintaining its self-repairing performance and improving the decorative effect and service life of the real stone paint.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A water-based environmentally friendly emulsion is prepared by the following steps:
[0009] Step 1: Grafting benzotriazole chloride onto sodium alginate microcapsules coated with bisphenol A epoxy resin through an acylation reaction to obtain benzotriazole-modified sodium alginate microcapsules.
[0010] Step 2: Styrene-acrylic emulsion, benzotriazole-modified sodium alginate microcapsules, microcapsule corrosion inhibitor, vermiculite powder and diphenylimidazole are stirred and mixed to obtain a water-based environmentally friendly emulsion.
[0011] Furthermore, the usage ratio of styrene acrylic emulsion, benzotriazole modified sodium alginate microcapsules, microcapsule corrosion inhibitor, vermiculite powder and diphenylimidazole is 3-4L: 300-400g: 200-300g: 10-12g: 14-15g.
[0012] Furthermore, the benzotriazole-modified sodium alginate microcapsules in step 1 are specifically prepared by the following steps:
[0013] Add benzotriazole chloride and tetrahydrofuran into a reactor, stir at 40-45°C and 400-500 r / min for 30-40 minutes, then add sodium alginate microcapsules and triethylamine, continue stirring and reacting for 12-14 hours. After the reaction is completed, filter, wash the filter cake with sodium bicarbonate solution and deionized water for 2-3 times respectively, and dry it in vacuum at 60-80°C for 1-2 hours to obtain benzotriazole-modified sodium alginate microcapsules.
[0014] Furthermore, the usage ratio of benzotriazole chloride, tetrahydrofuran, sodium alginate microcapsules and triethylamine is 1-2 kg: 5-6 L: 3-4 kg: 50-60 g.
[0015] Furthermore, sodium alginate microcapsules are prepared by the following steps:
[0016] Sodium alginate and deionized water are added to a reactor, stirred at 60-70°C and 400-500 r / min for 30-40 minutes, then bisphenol A epoxy resin and sodium dodecylbenzene sulfonate are added, stirring is continued for 2-3 hours, and then a calcium chloride solution with a mass fraction of 30-40% is added dropwise, stirring is continued for 1-2 hours, and the mixture is filtered. The filter cake is washed with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dried at 60-80°C for 1-2 hours to obtain sodium alginate microcapsules.
[0017] Furthermore, sodium alginate, deionized water, bisphenol A epoxy resin, sodium dodecylbenzene sulfonate and calcium chloride solution 2-3 kg: 2-3 L: 1-2 L: 120-130 mL: 4-5 L.
[0018] Further, benzotriazole chloride is prepared by the following steps:
[0019] Add terephthaloyl chloride and dichloromethane to a reactor, stir at 40-45°C and 400-500 r / min for 30-40 minutes, then add 1-hydroxybenzotriazole and triethylamine, and continue stirring for 3-4 hours. After the reaction is completed, remove dichloromethane by rotary evaporation, wash the product with deionized water 2-3 times, and vacuum dry at 60-80°C for 1-2 hours to obtain benzotriazole chloride.
[0020] Furthermore, the usage ratio of terephthaloyl chloride, dichloromethane, 1-hydroxybenzotriazole and triethylamine is 1-2 kg: 4-5 L: 2-3 kg: 120-140 g.
[0021] Furthermore, the microcapsule corrosion inhibitor in step 2 is specifically prepared by the following steps:
[0022] The corrosion inhibitor and a chitosan solution with a mass fraction of 10-20% are added to a reactor, ultrasonically dispersed at 40-50° C. for 40-50 minutes, and then a potassium chloride solution with a concentration of 0.5-0.6 mol / L is added to adjust the pH value to 5.5. The mixture is centrifuged at 1000-1200 r / min for 5-6 minutes, filtered, and the precipitate is collected. The precipitate is washed with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dried at 60-80° C. for 1-2 hours to obtain a microcapsule corrosion inhibitor.
[0023] Furthermore, the usage ratio of the corrosion inhibitor, the chitosan solution and the potassium chloride solution is 200-300 g: 4-5 L: 200-300 mL.
[0024] Furthermore, the corrosion inhibitor is prepared by the following steps:
[0025] Tetrabutyl titanate, tetraethyl silicate, anhydrous ethanol and glacial acetic acid are added into a reactor, stirred at 20-25°C and 400-500 r / min for 30-40 minutes, then histidine, anthocyanin, caffeic acid and deionized water are added, stirring is continued for 1-2 hours, vacuum impregnation is performed for 2-3 hours, and filtering is performed. The filter cake is washed with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dried at 60-80°C for 1-2 hours to obtain a corrosion inhibitor.
[0026] Furthermore, the usage ratio of tetrabutyl titanate, tetraethyl silicate, anhydrous ethanol, glacial acetic acid, histidine, anthocyanin, caffeic acid and deionized water is 800-900 mL: 700-800 mL: 3-4 L: 30-40 mL: 120-140 g: 60-70 g: 60-70 g: 3-4 L.
[0027] Beneficial effects of the present invention:
[0028] 1. The aqueous environmentally friendly emulsion prepared by the present invention contains benzotriazole-modified sodium alginate microcapsules with a sodium alginate shell and surface-grafted benzotriazole chloride. The benzotriazole chloride can reduce the probability of oxidation and rupture of the sodium alginate shell, protect the repair material in the sodium alginate microcapsules, and thus effectively maintain its self-repairing properties. This aqueous environmentally friendly emulsion is used in real stone paint, has outstanding self-repairing properties, strong aging resistance, is not prone to yellowing after long-term use, has good anti-pollution properties, a dense and smooth surface, is difficult for pollutants to adhere, has strong adhesion, is not easy to peel off, and can improve the decorative effect and service life of the real stone paint.
[0029] 2. The benzotriazole-modified sodium alginate microcapsules of the present invention are obtained by using an acrylic acid-modified epoxy resin as a core layer and sodium alginate as a shell layer, and grafting benzotriazole chloride on the surface. The acyl chloride group of the benzotriazole chloride undergoes an acylation reaction with the hydroxyl groups on the surface of the sodium alginate microcapsules, thereby retaining the carboxyl groups on the surface of the sodium alginate microcapsules. Benzotriazole can absorb ultraviolet energy, causing hydrogen bonds to break and converting them into harmless heat energy or low-energy radiation release. However, due to weak intermolecular forces, it is easy to migrate to the coating surface due to thermal motion during long-term use and be grafted on the surface of the sodium alginate microcapsules. The benzotriazole is fixed by the sodium alginate microcapsules to avoid migration. In addition, the benzotriazole can effectively protect the precise release of the sodium alginate microcapsules, avoiding the microcapsules from rupturing due to oxidation of the sodium alginate shell under sunlight. In addition, the benzene ring structure and steric hindrance effect in the benzotriazole can increase the hydrophobicity of the sodium alginate shell, preventing it from being swollen by water in advance when dispersed in an aqueous emulsion.
[0030] 3. Benzotriazole chloride combines with the hydroxyl groups on the surface of sodium alginate microcapsules through the acyl chloride group, thereby retaining the strongly hydrophilic carboxyl groups. The formation of sodium alginate microcapsules is mainly achieved through the cross-linking effect between the carboxyl groups and the calcium ions in calcium chloride. The calcium ions are bound to the GG fragments of sodium alginate through four coordination bonds. When the carboxyl groups of sodium alginate are grafted, the steric hindrance and charge state of the 5-carboxyl group are changed, weakening its coordination ability with calcium ions, resulting in a decrease in the degree of cross-linking. The retained carboxyl groups can avoid affecting the cross-linking structure of the sodium alginate microcapsules, thereby maintaining the strength of the microcapsules and making them less prone to rupture. When the coating ruptures due to long-term use or external force, the sodium alginate microcapsules in the coating rupture, releasing the bisphenol A epoxy resin therein, which comes into contact with the curing agent diphenylimidazole to repair the coating.
[0031] 4. The microcapsule corrosion inhibitor of the present invention impregnates histidine, anthocyanin and caffeic acid into the pores of titanium dioxide and silicon dioxide, and then uses chitosan to coat them. The coating effect of chitosan can significantly improve the effect of the corrosion inhibitor by diffusion in the pores, thereby extending the corrosion resistance time of the real stone paint. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0033] Example 1: A water-based environmentally friendly emulsion is prepared by the following steps:
[0034] S1: Add 2 kg of sodium alginate and 2 L of deionized water into a reactor, stir at 60 ° C and 400 r / min for 30 min, then add 1 L of bisphenol A epoxy resin and 120 mL of sodium dodecylbenzenesulfonate, continue stirring for 2 h, then dropwise add 4 L of 30% calcium chloride solution, continue stirring for 1 h, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, and dry it in a vacuum at 60 ° C for 1 h to obtain sodium alginate microcapsules.
[0035] The carboxyl groups on the surface of sodium alginate are cross-linked with the calcium ions in calcium chloride, thereby coating the acrylic acid-modified epoxy resin to form sodium alginate microcapsules.
[0036] S2: Add 1 kg of terephthaloyl chloride and 4 L of dichloromethane into a reactor, stir at 40°C and 400 r / min for 30 min, then add 2 kg of 1-hydroxybenzotriazole and 120 g of triethylamine, and continue stirring for 3 h. After the reaction is completed, remove the dichloromethane by rotary evaporation, wash the product with deionized water twice, and dry it in vacuo at 60°C for 1 h to obtain benzotriazole chloride.
[0037] The two acyl chloride groups of terephthaloyl chloride have high reactivity. In the polar solvent dichloromethane, the hydroxyl group of 1-hydroxybenzotriazole undergoes acylation reaction with the acyl chloride group. The hydroxyl group acts as a nucleophile to react with the acyl chloride group at one end of the acyl chloride benzotriazole, thereby retaining the acyl chloride group at one end.
[0038] S3: Add 1 kg of benzotriazole chloride and 5 L of tetrahydrofuran into the reactor, stir at 40°C and 400 r / min for 30 min, then add 3 kg of sodium alginate microcapsules and 50 g of triethylamine, and continue stirring and reacting for 12 h. After the reaction is completed, filter and wash the filter cake twice with sodium bicarbonate solution and deionized water respectively, and dry it in vacuum at 60°C for 1 h to obtain benzotriazole-modified sodium alginate microcapsules.
[0039] The acyl chloride groups of benzotriazole chloride react with the hydroxyl groups on the surface of the sodium alginate microcapsules to undergo acylation reaction. Since the nucleophilicity of the hydroxyl groups is stronger than that of the carboxylic acid groups, the hydroxyl groups are preferentially acylated, and some of the carboxyl groups react to form acid anhydrides, which are hydrolyzed in the subsequent washing process, thereby retaining the carboxyl groups on the surface of the sodium alginate microcapsules.
[0040] S4: Add 800mL of tetrabutyl titanate, 700mL of tetraethyl silicate, 3L of anhydrous ethanol and 30mL of glacial acetic acid into the reactor, stir at 20℃ and 400r / min for 30min, then add 120g of histidine, 60g of anthocyanin, 60g of caffeic acid and 3L of deionized water, continue stirring for 1h, vacuum impregnate for 2h, filter, wash the filter cake with deionized water and anhydrous ethanol twice, respectively, and vacuum dry at 60℃ for 1h to obtain a corrosion inhibitor; add 200g of corrosion inhibitor and 4L of 10% chitosan solution into the reactor, ultrasonically disperse at 40℃ for 40min, then add 200mL of 0.5mol / L potassium chloride solution to adjust the pH to 5.5, centrifuge at 1000r / min for 5min, filter, collect the precipitate, wash the precipitate with deionized water and anhydrous ethanol twice, respectively, and vacuum dry at 60℃ for 1h to obtain a microcapsule corrosion inhibitor.
[0041] Histidine, anthocyanin, and caffeic acid serve as natural organic corrosion inhibitors, which enter the pores of titanium dioxide and silicon dioxide through impregnation and are then coated with chitosan. The chitosan coating can significantly improve the effectiveness of the corrosion inhibitors in the pores through diffusion.
[0042] S5: 3-4 L of styrene-acrylic emulsion, 300 g of benzotriazole-modified sodium alginate microcapsules, 200 g of microcapsule corrosion inhibitor, 10 g of vermiculite powder and 14 g of diphenylimidazole as a curing agent were added to a reactor, stirred at 20°C and 400 r / min for 30 min, and mixed evenly to obtain a water-based environmentally friendly emulsion.
[0043] Example 2: A water-based environmentally friendly emulsion is prepared by the following steps:
[0044] S1: Add 2.3 kg of sodium alginate and 2.5 L of deionized water into a reactor, stir at 65 ° C and 450 r / min for 35 min, then add 1.5 L of bisphenol A epoxy resin and 125 mL of sodium dodecylbenzene sulfonate, continue stirring for 2.5 h, then add dropwise 4.5 L of 35% calcium chloride solution, continue stirring for 1.5 h, filter, wash the filter cake with deionized water and anhydrous ethanol twice, respectively, and dry in vacuo at 70 ° C for 1.5 h to obtain sodium alginate microcapsules.
[0045] S2: Add 1.5 kg of terephthaloyl chloride and 4.5 L of dichloromethane into a reactor, stir at 42.5 ° C and 450 r / min for 35 minutes, then add 2.5 kg of 1-hydroxybenzotriazole and 130 g of triethylamine, and continue stirring for 3.5 hours. After the reaction is completed, remove dichloromethane by rotary evaporation, wash the product with deionized water twice, and vacuum dry at 70 ° C for 1.5 hours to obtain benzotriazole chloride.
[0046] S3: Add 1.5 kg of benzotriazole chloride and 5.6 L of tetrahydrofuran into the reactor, stir at 42.5 ° C and 450 r / min for 35 minutes, then add 3.4 kg of sodium alginate microcapsules and 55 g of triethylamine, and continue stirring to react for 13 hours. After the reaction is completed, filter and wash the filter cake twice with sodium bicarbonate solution and deionized water respectively, and dry it in vacuum at 70 ° C for 1.5 hours to obtain benzotriazole-modified sodium alginate microcapsules.
[0047] S4: 850 mL of tetrabutyl titanate, 750 mL of tetraethyl silicate, 3.5 L of anhydrous ethanol and 35 mL of glacial acetic acid were added to the reactor and stirred at 22.5 ° C and 450 r / min for 35 min. Then, 130 g of histidine, 65 g of anthocyanin, 65 g of caffeic acid and 3.5 L of deionized water were added and stirred for 1.5 h. The mixture was vacuum impregnated for 2.3 h and filtered. The filter cake was washed with deionized water and anhydrous ethanol for 2-3 times respectively and vacuum dried at 60-80 ° C for 1-2 h, to obtain a corrosion inhibitor; 200-300 g of the corrosion inhibitor and 4.5 L of a 15% chitosan solution by mass were added to a reactor, ultrasonically dispersed at 45° C. for 45 min, and then 250 mL of a 0.55 mol / L potassium chloride solution was added to adjust the pH value to 5.5. The mixture was centrifuged at 1100 r / min for 5.5 min, filtered, and the precipitate was collected. The precipitate was washed twice with deionized water and anhydrous ethanol, respectively, and vacuum dried at 70° C. for 1.2 h to obtain a microcapsule corrosion inhibitor.
[0048] S5: 3-4 L of styrene-acrylic emulsion, 350 g of benzotriazole-modified sodium alginate microcapsules, 250 g of microcapsule corrosion inhibitor, 11 g of vermiculite powder and 14.5 g of diphenylimidazole as a curing agent were added to a reactor, stirred at 22.5°C and 450 r / min for 35 min, and mixed evenly to obtain a water-based environmentally friendly emulsion.
[0049] Example 3: A water-based environmentally friendly emulsion is prepared by the following steps:
[0050] S1: Add 3 kg of sodium alginate and 3 L of deionized water into a reactor, stir at 70 ° C and 500 r / min for 40 minutes, then add 2 L of bisphenol A epoxy resin and 130 mL of sodium dodecylbenzene sulfonate, continue stirring for 3 hours, then dropwise add 4-5 L of 40% calcium chloride solution, continue stirring for 2 hours, filter, wash the filter cake with deionized water and anhydrous ethanol three times respectively, and vacuum dry at 80 ° C for 2 hours to obtain sodium alginate microcapsules.
[0051] S2: Add 2 kg of terephthaloyl chloride and 5 L of dichloromethane into a reactor, stir at 45°C and 500 r / min for 40 min, then add 3 kg of 1-hydroxybenzotriazole and 140 g of triethylamine, and continue stirring for 4 h. After the reaction is completed, remove the dichloromethane by rotary evaporation, wash the product with deionized water three times, and dry it in vacuo at 80°C for 2 h to obtain benzotriazole chloride.
[0052] S3: Add 2 kg of benzotriazole chloride and 6 L of tetrahydrofuran into the reactor, stir at 45 ° C and 500 r / min for 40 min, then add 4 kg of sodium alginate microcapsules and 60 g of triethylamine, and continue stirring to react for 14 h. After the reaction is completed, filter and wash the filter cake with sodium bicarbonate solution and deionized water three times respectively, and dry it in vacuum at 80 ° C for 2 h to obtain benzotriazole-modified sodium alginate microcapsules.
[0053] S4: Add 900 mL of tetrabutyl titanate, 800 mL of tetraethyl silicate, 4 L of anhydrous ethanol and 40 mL of glacial acetic acid to the reactor, stir at 25 ° C and 500 r / min for 40 min, then add 140 g of histidine, 70 g of anthocyanin, 70 g of caffeic acid and 4 L of deionized water, continue stirring for 2 h, vacuum impregnate for 3 h, filter, wash the filter cake with deionized water and anhydrous ethanol respectively 2-3 times, and vacuum dry at 60-80 ° C for 1-2 h , obtaining a corrosion inhibitor; adding 200-300 g of the corrosion inhibitor and 5 L of a 20% chitosan solution by mass into a reactor, ultrasonically dispersing at 50° C. for 50 min, then adding 300 mL of a 0.6 mol / L potassium chloride solution to adjust the pH value to 5.5, centrifuging at 1200 r / min for 6 min, filtering, collecting the precipitate, washing the precipitate with deionized water and anhydrous ethanol three times, respectively, and vacuum drying at 80° C. for 2 h to obtain a microcapsule corrosion inhibitor.
[0054] S5: 3-4 L of styrene-acrylic emulsion, 400 g of benzotriazole-modified sodium alginate microcapsules, 300 g of microcapsule corrosion inhibitor, 12 g of vermiculite powder and 15 g of diphenylimidazole as a curing agent were added to a reactor, stirred at 25°C and 500 r / min for 40 min, and mixed evenly to obtain a water-based environmentally friendly emulsion.
[0055] Comparative Example 1: In Example 3, without going through step S2, the benzotriazole chloride in step S3 is directly replaced by 1-hydroxybenzotriazole in step S2, and the rest remain unchanged to prepare an aqueous environmentally friendly emulsion.
[0056] Comparative Example 2: In Example 3, without the treatment in step S2, the 1-hydroxybenzotriazole and the sodium alginate microcapsules in step S2 were directly mixed in a mass ratio of 2:4, and the rest remained unchanged to prepare an aqueous environmentally friendly emulsion.
[0057] Comparative Example 3: In Example 3, the microcapsule corrosion inhibitor in step S5 was replaced by the corrosion inhibitor of the same mass in step S4, and the rest remained unchanged to prepare an aqueous environmentally friendly emulsion.
[0058] The water-based environmentally friendly emulsions obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were respectively prepared into real stone paints for performance testing: 200 g of water-based environmentally friendly emulsion, 900 g of natural colored sand, 30 g of rock flakes, 5 g of ethylene glycol, 1 g of hydroxyethyl cellulose, 8 g of 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 1 g of 2-amino-2-methyl-1-propanol, 2 g of BYK-024 water-based defoamer, 2 g of Wacker BS1306CN silicone water repellent, 2 g of Rohm and Haas LXE fungicide and 8 g of deionized water were added to a reactor, stirred at 25 ° C and 500 r / min for 40 min, mixed evenly, and obtained a real stone paint.
[0059] Place the real stone paint at a distance of 60 cm between the gun muzzle and the mortar block board, and spray at a pressure of 0.8 Pa / cm 2 Under the conditions of , spraying was carried out, spraying was carried out twice, the thickness of each spraying was 1mm, the total thickness of the paint film was 2mm, and it was cured for 14 days at a temperature of 25°C and a humidity of 65% to obtain a test plate. Then, according to the standard of JG / T24-2000 "Synthetic resin emulsion sand wall building coating", the stain resistance, temperature change resistance, tensile bonding strength test and the tensile bonding strength test after the specimen was immersed in water were carried out.
[0060] Aging resistance test: Refer to GB / T 1865-1997 Paints and varnishes - Artificial aging and artificial radiation exposure (filtered xenon arc radiation) standard to test the aging resistance of the test panel.
[0061] Repair rate test: According to JG / T24-2018 standard, a safety single-sided blade with a length of 2 cm and a depth of about 100 μm was used to create the same number of cracks on the test panel. After curing under standard conditions for 7 days, a 50 mm bending test was performed on the paint film using a flexibility tester (Biaogeda, model: BGD590). The number of cracks on the paint film surface was used to calculate the repair rate of the paint film. The repair rate of the paint film = 1-number of cracks / number of artificially created cracks. The test was conducted in accordance with standard JG / T24-2018.
[0062] Stain resistance test: Mix 100g of fly ash and 100g of water evenly. Take two test panels, place the coated side down in a 1:1 fly ash and water mixture, and place them horizontally for 5 seconds. Then take them out and dry them naturally in a standard environment for 2 hours. Then, perform a flushing test according to the test apparatus and test method in GB / T 9780-1988. After 5 cycles, evaluate according to the method in the basic gray card (GB250-1995). It consists of 5 pairs of matte gray small cards and is divided into 5 levels according to the distinguishable color difference, namely 5, 4, 3, 2, and 1. Observe according to the visual colorimetry method in GB / T1766-1995.
[0063] Temperature denaturation resistance test: The test shall be carried out in accordance with the provisions of JG / T25. At least two of the three test panels shall be free of powdering, cracking, peeling, bulging and obvious discoloration.
[0064] The results are shown in Table 1:
[0065] Table 1 Real stone paint performance test results
[0066]
[0067] As can be seen from Table 1, the water-based environmentally friendly emulsions obtained in Examples 1 to 3 are prepared into real stone paints, and the stain resistance, temperature change resistance, tensile bonding strength after immersion in water, aging resistance and repair rate are significantly better than those of the comparative example, indicating that the water-based environmentally friendly emulsions prepared by the present invention are used in real stone paints, and have outstanding self-repairing properties; strong aging resistance, and are not easy to yellow after long-term use under ultraviolet rays; good anti-pollution performance, a dense and smooth surface, and pollutants are difficult to adhere; strong adhesion, and are not easy to peel off.
[0068] In Comparative Example 1, step S3 is not performed, and the benzotriazole chloride is replaced with 1-hydroxybenzotriazole. By chlorinating 1-hydroxybenzotriazole, the acyl chloride group is combined with the hydroxyl group on the surface of the sodium alginate microcapsule, thereby retaining the strong hydrophilic carboxyl group, which can avoid affecting the cross-linking structure of the sodium alginate microcapsule, thereby maintaining the strength of the microcapsule and not easily breaking. When replaced with 1-hydroxybenzotriazole, the hydroxyl group on the surface of 1-hydroxybenzotriazole will occupy some of the carboxyl sites on the surface of the sodium alginate, thereby reducing the degree of cross-linking between the carboxyl group and the calcium ion in the sodium alginate microcapsule, thereby affecting the self-healing ability of the benzotriazole-modified sodium alginate microcapsule.
[0069] In Comparative Example 2, step S3 is not performed, and 1-hydroxybenzotriazole and sodium alginate microcapsules are evenly mixed. Due to the weak intermolecular force, 1-hydroxybenzotriazole is easily migrated to the coating surface due to thermal movement during long-term use. If the coating is exposed to sunlight for a long time, it is easy to cause a decrease in ultraviolet resistance, which in turn causes the coating to yellow and fall off. Through a chemical grafting reaction, 1-hydroxybenzotriazole is grafted on the surface of the sodium alginate microcapsules, and the sodium alginate microcapsules are used to fix the benzotriazole, thereby avoiding migration.
[0070] In Comparative Example 3, the microcapsule corrosion inhibitor is replaced with a corrosion inhibitor and coated with chitosan. The coating effect of chitosan can significantly improve the effect of the corrosion inhibitor in the pores by diffusion, thereby extending the corrosion resistance time of the real stone paint. Chitosan has a sustained-release function, which can avoid the loss of corrosion-inhibiting components due to physical diffusion during the preparation of the real stone paint.
[0071] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations can be made to the embodiments without departing from the principles and spirit of the invention.
Claims
1. A water-based environmentally friendly emulsion, characterized in that: The aqueous environmentally friendly emulsion is prepared by the following steps: Step 1: Grafting benzotriazole chloride onto sodium alginate microcapsules coated with bisphenol A epoxy resin through an acylation reaction to obtain benzotriazole-modified sodium alginate microcapsules; Step 2: Stirring and mixing the styrene-acrylic emulsion, benzotriazole-modified sodium alginate microcapsules, microcapsule corrosion inhibitor, vermiculite powder and diphenylimidazole to obtain a water-based environmentally friendly emulsion; The usage ratio of the styrene-acrylic emulsion, the benzotriazole-modified sodium alginate microcapsules, the microcapsule corrosion inhibitor, the vermiculite powder and the diphenylimidazole is 3-4L: 300-400g: 200-300g: 10-12g: 14-15g.
2. The water-based environmentally friendly emulsion according to claim 1, characterized in that: The benzotriazole-modified sodium alginate microcapsules described in step 1 are specifically prepared by the following steps: Add benzotriazole chloride and tetrahydrofuran into a reactor, stir at 40-45°C and 400-500 r / min for 30-40 min, then add sodium alginate microcapsules and triethylamine, continue stirring and reacting for 12-14 h. After the reaction is completed, filter, wash, and vacuum dry to obtain benzotriazole-modified sodium alginate microcapsules.
3. The water-based environmentally friendly emulsion according to claim 2, characterized in that: The usage ratio of the benzotriazole chloride, tetrahydrofuran, sodium alginate microcapsules and triethylamine is 1-2 kg: 5-6 L: 3-4 kg: 50-60 g.
4. The water-based environmentally friendly emulsion according to claim 2, characterized in that: The sodium alginate microcapsules are prepared by the following steps: Sodium alginate and deionized water are added to a reactor, stirred at 60-70°C and 400-500 r / min for 30-40 minutes, then bisphenol A epoxy resin and sodium dodecylbenzene sulfonate are added, stirring is continued for 2-3 hours, and then a 30-40% by mass calcium chloride solution is added dropwise, stirring is continued for 1-2 hours, and the mixture is filtered. The filter cake is washed with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dried at 60-80°C for 1-2 hours to obtain sodium alginate microcapsules; The sodium alginate, deionized water, bisphenol A epoxy resin, sodium dodecylbenzene sulfonate and calcium chloride solution are 2-3 kg: 2-3 L: 1-2 L: 120-130 mL: 4-5 L.
5. The water-based environmentally friendly emulsion according to claim 2, characterized in that: The benzotriazole chloride is prepared by the following steps: Add terephthaloyl chloride and dichloromethane to a reactor, stir at 40-45°C and 400-500 r / min for 30-40 minutes, then add 1-hydroxybenzotriazole and triethylamine, and continue stirring for 3-4 hours. After the reaction is completed, remove dichloromethane by rotary evaporation, wash the product with deionized water 2-3 times, and vacuum dry to obtain benzotriazole chloride.
6. The water-based environmentally friendly emulsion according to claim 5, characterized in that: The usage ratio of terephthaloyl chloride, dichloromethane, 1-hydroxybenzotriazole and triethylamine is 1-2 kg: 4-5 L: 2-3 kg: 120-140 g.
7. The water-based environmentally friendly emulsion according to claim 1, characterized in that: The microcapsule corrosion inhibitor in step 2 is specifically prepared by the following steps: The corrosion inhibitor and 10-20 wt% chitosan solution were added to a reactor, ultrasonically dispersed at 40-50° C. for 40-50 min, and then a 0.5-0.6 mol / L potassium chloride solution was added to adjust the pH value to 5.
5. The mixture was centrifuged at 1000-1200 r / min for 5-6 min, filtered, and the precipitate was collected. The precipitate was washed with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dried to obtain a microcapsule corrosion inhibitor. The usage ratio of the corrosion inhibitor, chitosan solution and potassium chloride solution is 200-300 g: 4-5 L: 200-300 mL.
8. The water-based environmentally friendly emulsion according to claim 7, characterized in that: The corrosion inhibitor is prepared by the following steps: Tetrabutyl titanate, tetraethyl silicate, anhydrous ethanol and glacial acetic acid are added into a reactor, stirred at 20-25° C. and 400-500 r / min for 30-40 min, then histidine, anthocyanin, caffeic acid and deionized water are added, stirring is continued for 1-2 h, vacuum impregnation is performed for 2-3 h, filtration, washing and vacuum drying are performed to obtain a corrosion inhibitor.
9. The water-based environmentally friendly emulsion according to claim 8, characterized in that: The dosage ratio of tetrabutyl titanate, tetraethyl silicate, anhydrous ethanol, glacial acetic acid, histidine, anthocyanin, caffeic acid and deionized water is 800-900 mL: 700-800 mL: 3-4 L: 30-40 mL: 120-140 g: 60-70 g: 60-70 g: 3-4 L.
10. Use of the water-based environmentally friendly emulsion according to claim 1 in real stone paint.
Citation Information
Patent Citations
A water-based environmentally friendly anti-corrosion coating
CN116426193B
Cited By
High-weatherability stone-imitating real stone paint and preparation method thereof
CN122609123A